A não-cumulatividade do ICMS: uma aplicação da teoria sobre as regras do direito e as regras dos jogos - Lunardelli, Pedro Guilherme Accorsi (2007)
The objective of this work is the formularization of a theory on the legal phenomena that involves the subject of Non-Cumulative of the ICMS (Tax on Distribution of Goods and Services), taking as foundation the thought of the Professor Gregorio Robles, displayed in his book Las Reglas del Derecho y las Reglas del Juego. According to the mentioned Professor, the legal system can be understood by three types of rules, thus called Ontics, responsible for the setting of the minimum elements of this system, the techniques, that establish the procedures for creation of other rules and, finally, the typically deontics rules, such function is regulating the behavior of the human being. From these concepts, we distinguish the rules ontic and technique of the Non-Cumulative, in order to compare it with the deontic rule of the ICMS, also known as head rule. This segmentation allowed us to identify the elements and procedures that compose the rule technique of Non-Cumulative, as well as rewriting the elements of the head rule of that tax and, still, to analyze what way the related value to the non-cumulative influences both one and the other rule